The Influence of Scramble Method to Increase Students' Interest in Learning History - Acim Acim; Muhammad Rijal Fadli; Jems Sopacua (Yayasan Keluarga Guru Mandiri, 2023)
The scramble method can help students understand history learning material easily, but not many teachers have implemented it in history learning. The purpose of this research was to find the effect of the scramble method in history learning to increase students' interest in learning history. The quantitative method used is a quasi-experimental non-equivalent control group design and divides the class into two groups, namely experimental and control. This study used a population of class X SMA students in Ambon, with a total sample of 104. The sampling technique used cluster sampling, and data collection used observations, interviews, and instruments. In analysing the test data, the independent sample t-test and the N-gain score test were used to see changes. The results showed that the scramble method in learning had a good influence on increasing students' interest in learning history as evidenced by the independent sample t-test test with a significance value of 0.000 0.05, and the N-gain score test which was included in the medium criteria. The scramble method in history learning is an innovation applied by history teachers so that learning objectives are achieved so that history learning will be more meaningful.